Assessment Of Current Status Of Medicinal Plants Diversity From Bathinda District, Punjab (India) - Arora, Bhumika; Kaur, Kamaldeep; Modi, Gajanand (Journal of Neonatal Surgery, 2025)
Present study aimed to update the current status of medicinal plants diversity in district Bathinda, Punjab (India). In this study, we aimed to explore and document the high-valued plant diversity, both wild and cultivated, and the traditional knowledge associated with these plants. This was accomplished through a participatory approach involving local communities, where we collected data using semi-structured questionnaires. The study highlights the importance of integrating local knowledge with scientific research to enhance conservation efforts and promote sustainable utilization of plant resources. By engaging with the community, we were able to capture valuable insights that reflect the cultural significance and practical applications of these plants in daily life. Moreover, during the biodiversity evaluation, it was noted that various medicinal plants thrived in these villages. Residents of the villages possess extensive knowledge regarding the plants based on traditional healthcare methods, and they consistently opt for local medicinal plants for treating minor ailments in both humans and animals. Predominantly, herb species (173) were utilized in traditional remedies, followed by shrubs (51), trees (50), climbers (14) etc. In the current research, it was noted that there is a growing trend of biodiversity in this region, due to the collaborative efforts of local residents, the forest department, and the Punjab Biodiversity Board.